2018
DOI: 10.5171/2018.683208
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors Influencing the Leadership Performance of Saudi’s Healthcare Sector

Abstract: The purpose of this article is to identify the aspects that relate to performance level; including enablers and inhibitors that influence leadership performance in the healthcare sector of the Kingdom of Saudi Arabia (KSA). A grounded research methodology and an action research approach that was 'issue focused' were used to gain the perceptions of the participants from the organisational culture as empirical data. The overall trends observed in the collected data emphasize the important role of culture in shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…These factors refer to the dimensions of transformational and transactional leadership. Furthermore, the results of Algarni et al (2018) showed that 24 factors influenced leadership performance. Thanh and Anh (2015) presented that traits and skills influenced leadership style and effectiveness.…”
Section: Student Leadershipmentioning
confidence: 97%
“…These factors refer to the dimensions of transformational and transactional leadership. Furthermore, the results of Algarni et al (2018) showed that 24 factors influenced leadership performance. Thanh and Anh (2015) presented that traits and skills influenced leadership style and effectiveness.…”
Section: Student Leadershipmentioning
confidence: 97%
“…As a result, they feel less motivated at work and may experience burnout because they feel that their effort is unrecognized. Algarni et al [22] similarly suggested that the highest tiers of management should supervise the relationship between leaders and their followers to ensure that nurses are properly trained and not exposed to stress to enhance their job performance.…”
Section: Positive and Negative Impact Of The Factors On Developing Se...mentioning
confidence: 99%
“…Many leadership scholars have argued that followership concepts, styles, and behavior preferences of leaders may vary across cultures 7,24–27. Saudi Arabia is a country where culture has a major influence on the structure, employment, performance, and relationships between leaders and followers in organizations 28. Saudi culture is derived from two major sources: Islamic values and tribal traditions and customs 28,29.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 24 , 25 , 26 , 27 Saudi Arabia is a country where culture has a major influence on the structure, employment, performance, and relationships between leaders and followers in organizations. 28 Saudi culture is derived from two major sources: Islamic values and tribal traditions and customs. 28 , 29 In this unique cultural context, the nursing profession has confronted many challenges.…”
Section: Introductionmentioning
confidence: 99%